DISTRIBUTION PATTERNS OF THE SUPPLY CHAIN AND VALUE ADDITION OF COFFEE AGRIBUSINESS IN KADUAJA VILLAGE, GANDANGBATU SILLANAN DISTRICT, TANA TORAJA REGENCY - Rahmawati Rahmawati; Marhawati Marhawati; Agus Syam; Muhammad Jufri; Nur Halim (CV. ADIBA AISHA AMIRA, 2025)
This research aims to determine the flow pattern of the coffee agribusiness supply chain and calculate the added value of the coffee agroindustry in Kaduaja Village, Gandangbatu Sillanan District, Tana Toraja Regency. The research location was determined purposively, with respondents consisting of 9 coffee farmers, 3 coffee fruit collectors, 1 large-scale coffee fruit trader, and 7 coffee consumers, totaling 20 samples. The results of this study indicate that 1) there are five patterns of the coffee supply chain flow in Kaduaja Village, Gandangbatu Sillanan District, Tana Toraja Regency, where this mechanism has three flows: first, the product flow moves from upstream to downstream, namely from farmers-collecting traders-Bunga Seong Coffee (processor)-consumers. Second, the flow of money moves from downstream to upstream, that is, from consumers to Bunga Seong Coffee (processor), then to collecting traders, and finally to the farmers. Third, the flow of information that occurs between members of the supply chain is the price, flowing from Bunga Seong Coffee (processor) to the collecting traders and then to the farmers. 2) The added value of the coffee agroindustry reaches 22.00% of the output value. The contribution of income obtained by the labor involved in the coffee agroindustry is 4.16%, with labor income reaching Rp.10,000/kg. The profit margin of the coffee agroindustry is 95.833%, meaning that every 1.5 kg of coffee raw material can provide an added value of Rp.240,000/kg.